Kepastian Hukum Program Pengungkapan Sukarela Wajib Pajak Atas Surat Keterangan Batal Demi Hukum - Adi Rohman Fajar; Khalimi Khalimi; Hedwig Adianto Mau (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
The importance of taxes for the survival of the state makes the government must continuously strive to increase public participation, namely paying taxes by increasing awareness and tax compliance. In Indonesia, there are three types of tax collection systems, the first is the Self Assessment System in which taxpayers are given the trust to calculate, deposit and report their own tax payable; the second is the Official Assessment System where the government is given the authority to determine the amount of tax owed by the taxpayer and while the Withholding Assessment System is the amount of tax calculated by a third party who is not a taxpayer and is not a tax officer/fiscus. In this paper the authors use descriptive qualitative methods, the results of the research in this paper are where the Government gives confidence to the self-assessment system taxpayers to calculate their own taxes payable and regarding the legal certainty of the taxpayer's voluntary disclosure program on affidavits null and void in Indonesia.Keywords: Taxpayer; Legal certainty; Letter of Statement AbstrakPentingnya pajak bagi kelangsungan negara membuat pemerintah harus terus menerus berupaya meningkatkan peran serta masyarakat yaitu membayar pajak dengan meningkatkan kesadaran dan kepatuhan perpajakannya. Di Indonesia berlaku tiga jenis sistem pemungutan pajak yang pertama adalah Self Assessment System yang dimana wajib pajak diberikan kepercayaan untuk menghitung, menyetor dan melaporkan sendiri pajak terutangnya; kedua adalah Official Assessment System dimana pemerintah diberikan wewenang untuk menentukan besarnya pajak yang terutang oleh wajib pajak dan sementara Withholding Assessment System adalah besarnya pajak dihitung oleh pihak ketiga yang bukan wajib pajak dan bukan juga aparat pajak/fiskus. Dalam penulisan ini penulis menggunakan metode kualitatif deskriptif, hasil penelitian pada tulisan ini adalah dimana Pemerintah memberikan kepercayaan kepada wajib pajak Self Assessment System untuk menghitung sendiri pajak terhutang dan mengenai kepastian hukum program pengungkapan sukarela wajib pajak atas surat keterangan batal demi hukum di Indonesia.Kata Kunci: Wajib Pajak; Kepastian Hukum; Surat Keterangan